The Role of Age and Social Motivation in Developmental Transitions in Young and Old Adulthood - Nikitin, Jana; Burgermeister, Lea C.; Freund, Alexandra M. (Frontiers in Psychology, 2012)
Two diary studies investigated the role of social approach and avoidance motivation in important developmental transitions in young and old adulthood. Study 1 comprised a sample of young adults (N = 93, M = 21.5 years) who moved out of their parental homes. The sample of Study 2 consisted of older adults (N = 69, M = 76.95 years) who moved into senior housing. In both studies, participants reported their habitual social approach and avoidance motives as well as their daily social experience and subjective well-being over the course of two weeks. In line with the literature, social approach motives and age were related to higher subjective well-being, whereas social avoidance motives were negatively associated with subjective well-being. Time since the transition was an important moderator of the association between social avoidance motives and negative outcomes. With increasing time from the transition, the negative effects of social avoidance motives decreased. The positive effects of social approach motives remained fairly stable over time. Importantly, age did not moderate any of the associations between social motivation and outcomes. Results are discussed in terms of transition-related instability and age-related stability.